REFORMS WITHOUT REFORMING: TRENDS IN LOCAL AND REGIONAL GOVERNANCE AND DECENTRALIZATION IN CROATIA - Đulabić, Vedran; Lopižić, Iva (Pravni zapisi, 2025)
The paper presents, analyzes, and discusses changes in the Croatian local self-government system and assesses their drivers, whether these changes can be con- sidered real reforms, and why certain changes occur and others do not. The paper covers a 30-year time span of local self-government development – from the early 1990s, when Croatia introduced a modern local self-government, through the 2000s when Croatia transitioned to the system based on political decentralization, to recent reform activities. The paper shows that there have been several “real” reforms that have raised and addressed very important issues, while other “reforms” can mostly be described as partial changes that occur when there is significant political will for them or under strong external pressure. Political actors and their role of veto players, together with path dependency, remain crucial explanatory factors of local self-government development in the past three decades in Croatia.
Keywords: Local Self-Government Reform; Decentralization; Local and Regional Self-Government in Croatia; Development Trends in Local and Regional Government